Chemotherapeutic nanoparticles for glioblastoma - Messina, Samantha; Zuchegna, Candida; Bruzzi, Mara (Frontiers in Oncology, 2025)
Therapeutic agents into the brain are a major challenge for treatment of brain cancer due to the blood-brain barrier (BBB) that prevents many drugs from reaching the brain. The deadliest form of brain cancer is glioblastoma (GBM), and its current standard treatment involves surgical removal of the tumor, followed by chemotherapy and radiotherapy. The main limitations of chemotherapy for brain tumors are BBB permeability, lack of specificity, and potential damage to healthy tissue. Enhanced molecular understanding of the underlying glioblastoma pathogenesis doesn’t lead to better therapeutic options. The emergence of nanotechnologies offers a promising solution, as controlled drug delivery using nanoparticles to bypass the BBB. Nanoparticles embrace a wide range of synthetic and natural biological materials effective in enhancing diagnostic and therapeutic efforts, alone or in combination with immunological, genetic, or cellular therapies. Lipid-based, inorganic, and polymeric nanoparticles are on the cutting edge of precision medicine for cancer as both therapeutic and diagnostic tools. Currently, there is no consensus on the most effective nanoparticle formulation for treating brain tumors, including their size, composition, targeting, and drug delivery mechanisms. Nanoparticles also have some drawbacks, including uncertain toxicity, reproducibility, and high cost. This short review provides a selection of primary research on nanoparticles as delivery chemotherapeutic systems, with a highlight on Photodynamic therapy (PDT) and radiotherapy (RT) combinatorial modalities. Here we critically examine the most significant research findings in the field of nanomedicine as applied to glioblastoma therapy, with a particular emphasis on chemotherapeutic nanoparticle (NP)-based drug delivery. In parallel, we provide an overview of the physicochemical properties of nanoparticles, informed by recent advances in their engineering, with a special focus on combinatorial strategies involving photodynamic therapy (PDT) and radiotherapy (RT). Our analysis focuses on highly potent anticancer drugs that are well characterized in terms of their pharmacokinetics and pharmacodynamics. The latest developments in immunotherapy and molecular-targeted treatments are intentionally excluded. Our viewpoint is grounded in the conventional yet highly effective chemotherapy-based delivery approach, which remains widely used against many of the most lethal human cancers. Despite being underrepresented in current literature, this strategy holds strong potential for clinical translation and competitiveness.